LOGISTIC ACTIVITIES IN BELARUS: TRENDS AND CHALLENGES - P. V. Bozhanov (Наука и техника)
Main results of investigations on logistics activities in the Republic of Belarus at year-end 2016 are presented in the paper. The paper identifies and analyzes basic components of this activity on the basis of economic evaluation of indices presented in annual State statistical reporting on logistics and transport and freight forwarding activities of the Republican organizations according to form 1-logistics (Mintrans – Ministry of Transport and Communications of the Republic of Belarus), a report of the Ministry of Transport and Communications of the Republic of Belarus on the results of the implementation of Republican Program for development of logistics systems and transit potential of the Republic of Belarus for the period of 2016–2020, World Bank reports on logistics performance index, some indices of logistics infrastructure position and also results of electronic questionnaire of the largest logistics centers of the Republic of Belarus. Methods of comparative analysis, generalization and economic analysis have been used in the process of research. The analysis has shown that a network of logistics centers with various specialization and forms of property are located and operating in all regions of the Republic of Belarus. Most of them are situated in the Minsk region near the II and IX trans-European transport corridors and in the Brest region near the border with Poland. Structure of the logistics centers includes temporary storage warehouses, customs warehouses, warehouses for general use, container terminals, car parking, customs clearance office, and automotive, railway and other cargo transport facilities. Indices of logistics activity in the Republic of Belarus demonstrate its development in 2016. Storage space of logistics centers and main financial and volumetric indices of logistics activity which are included in the State statistical reporting have been increased during in recent times. These facts testify to the demand for logistics capacity of the Republic of Belarus and its efficient economic and infrastructure development.